Capital structure determinants for arts nonprofits. Issue 4 (18th February 2021) - Charles, Cleopatra; Sloan, Margaret F.; Butler, John S.
Abstract: Nonprofit leaders use various strategies when making financial decisions and balancing current mission fulfillment with long‐term financial stability is a delicate act for nonprofit organizations. From a financial management perspective, nonprofit managers and executives looking to sustain a healthy organization must successfully manage the tension between pursuing the mission and preserving organizational and financial viability. This study explores potential factors that influence nonprofit arts organizations' decisions to issue financial debt and determine whether these organizations balance financial obligations by exercising pecking order or static trade‐off decisions. We use the DataArts database and investigate whether donor‐restricted endowments have an impact on financial debt of arts nonprofit organizations. Model estimates show that organizations with a donor‐restricted endowment are less likely to issue debt and have lower debt ratios on average. This study finds support for both pecking order theory and static trade‐off theory, which indicates that there is no one‐dominant capital structure theory to explain the capital structure of arts nonprofits.